Directional orbital angular momentum generator with enhanced vertical emission efficiency - Tran, Thang Q.; Kim, Sangin (Current Optics and Photonics, 2019)
We propose a ring resonator-based orbital angular momentum carrying vortex beam generator design with high vertical directional emission efficiency. By adopting a vertically asymmetric grating structure in the ring resonator, optimized for enhanced vertical emission, an emission efficiency in one direction reaches as high as 78%, exceeding the 50% theoretical limit of previously designed vertically symmetric grating-assisted ring resonator-based structures.
Keywords: Directional emission; Emission efficiencies; Generator design; Grating structures; Orbital angular momentum; Theoretical limits; Vertical emission; Vortex beams; Numerical modeling; Optical orbital angular momentum; Vortex beam